2018
DOI: 10.1002/wcc.509
|View full text |Cite
|
Sign up to set email alerts
|

Public engagement with climate imagery in a changing digital landscape

Abstract: Despite extensive exploration into the use of language in climate change communication, our understanding of the use of visual images, and how they relate to public perceptions of climate change, is less developed. A limited set of images have come to represent climate change, but rapid changes in the digital landscape, in the way media and information are created, conveyed, and consumed has changed the way climate change is visualized. We review the use of climate imagery in digital media (news and social med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 145 publications
2
100
0
6
Order By: Relevance
“…These impacts seemed structured around abstract terms such as the greenhouse effect and recurrent references to the Arctic, polar bears and melting ice, with only few mentions of locally relevant impacts that could directly affect the participants' lives in Sweden. These connotations are consistent with iconography that have been found to represent public perceptions of climate change, including polar bears, melting ice and globes (Doyle 2007;Smith & Joffe 2009;Manzo 2010b;Wang 2018). Focusing on climate impacts in geographically distant locations suggests that the participants -both in the individual mind map exercise and in the focus group discussions -reinforced the construction of climate change as a distant phenomenon, which is consistent with several studies on public perceptions of climate change (e.g.…”
Section: General Perceptions Of Climate Changesupporting
confidence: 87%
See 2 more Smart Citations
“…These impacts seemed structured around abstract terms such as the greenhouse effect and recurrent references to the Arctic, polar bears and melting ice, with only few mentions of locally relevant impacts that could directly affect the participants' lives in Sweden. These connotations are consistent with iconography that have been found to represent public perceptions of climate change, including polar bears, melting ice and globes (Doyle 2007;Smith & Joffe 2009;Manzo 2010b;Wang 2018). Focusing on climate impacts in geographically distant locations suggests that the participants -both in the individual mind map exercise and in the focus group discussions -reinforced the construction of climate change as a distant phenomenon, which is consistent with several studies on public perceptions of climate change (e.g.…”
Section: General Perceptions Of Climate Changesupporting
confidence: 87%
“…Climate change communication is a rapidly expanding research field, in which the majority of studies seek to identify effective ways to communicate climate change with lay audiences, among others, and to understand public perceptions of climate change (Wibeck 2014a;Wang et al 2018). Nevertheless, as Moser & Dilling (2007, 3) pointed out a decade ago when contemplating the question of how communication about climate change can facilitate social change: "The science of global warming is clear -why are they not listening?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate change communication field contributes fundamental insights on whether and how climate change messages' imaging and delivery can be used to enhance action (Brügger et al, ; Moser, ; Wang, Corner, Chapman, & Markowitz, ). TMT complements this discussion and offers insights on how implicit/explicit mortality threats trigger defenses and influence the measures' adoption across different worldviews and/or identities.…”
Section: Terror Management Theory and Climate Response: A Research Agmentioning
confidence: 99%
“…Past scholarship has mostly dealt with textual representations of climate issues on social media. Wang and colleagues note that there is a lack of published research on climate visuals found in social media (Wang, Corner, Chapman, & Markowitz, 2018). We developed a sampling frame of Twitter users representing key climate stakeholder groups (e.g., climate activist organizations and individuals, multinational institutions and individual representatives, mainstream and alternative media).…”
Section: Research-article20182018mentioning
confidence: 99%